Controlling the c-Si/a-Si:H interface in silicon heterojunction solar cells fabricated by HWCVD. (1st March 2017) - Agarwal, Mohit; Pawar, Abhijeet; Wadibhasme, Nilesh; Dusane, Rajiv
Highlights: Controlling the c-Si/a-Si:H through process variation during preparation by the HWCVD. Local epitaxy and roughness at the c-Si/a-Si:H interface yield poor cell performance. Large improvement in the blue response relates to good interface and a-Si:H layer. Abstract: This paper deals with the engineering of the hetero-interface between intrinsic amorphous silicon (i-a-Si:H) layer and the n-type crystalline silicon (c-Si) wafer during the fabrication of the Silicon Heterojunction (SHJ) solar cell by the Hot Wire Chemical Vapor Deposition technique. It is known that this interface and the associated surface passivation of the c-Si is key to obtaining high efficiency heterojunction solar cells. The monitoring of this interface was carried out using high-resolution transmission electron microscopy (HRTEM). The HRTEM data of the c-Si/a-Si:H interface reveals a drastic dependence on the filament temperature (Tf ) used during the deposition of the i-a-Si:H layer. Detailed analysis of the solar cell characteristics indicates that the cells where one has an abrupt crystalline/amorphous interface shows higher conversion efficiency compared to those where we have a rough and a defective interface or where there are indications of local epitaxy in the a-Si:H layer. The second parameter which was engineered is the bulk defect density of the intrinsic a-Si:H layer. Though the thickness of i-a-Si:H layer in case of SHJ solar cells is only around 5 nm and serves the purpose of passivating the dangling bonds on the c-Si wafer, the bulk defect density of this layer cannot be ignored. We have achieved a-Si:H films with acceptable bulk defect density without dilution of the silane gas with hydrogen. The bulk defect density of the i-a-Si:H layer has been determined by the constant photocurrent method (CPM) and is correlated to the performance of SHJ solar cells. A direct consequence of these control parameters was observed in the improvement of the external quantum efficiency near 600 nm wavelength region.